2012
DOI: 10.1590/s0004-282x2012001100010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nitric oxide levels in the hippocampus may play a role in learning and memory deficits in ovariectomized rats treated by a high dose of estradiol

Abstract: The effects of a high estradiol dose on memory and on nitric oxide metabolites in hippocampal tissues were investigated. Sham-Est and OVX-Est Groups were treated with 4 mg/kg of estradiol valerate for 12 weeks. Time latency and path length were significantly higher in the Sham-Est and OVX-Est Groups than in the Sham and OVX Groups, respectively (p<0.001). The animals in the Sham-Est and OVX-Est Groups spent lower time in the target quadrant (Q1) than those of the Sham and OVX Groups during the probe trial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 31 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…NO metabolites (NO 2 /NO 3 ) were measured according to the Griess reagent methods. In brief, after adding 100 μl supernatant to the Griess reagent, contents were transferred to a 96-well flat-bottomed micro-plate and absorbance was read at 520 nm using a micro-plate reader, and the final values were calculated from standard calibration plots [27][28][29].…”
Section: Determination Of Mda Total Thiol and No Metabolitesmentioning
confidence: 99%
“…NO metabolites (NO 2 /NO 3 ) were measured according to the Griess reagent methods. In brief, after adding 100 μl supernatant to the Griess reagent, contents were transferred to a 96-well flat-bottomed micro-plate and absorbance was read at 520 nm using a micro-plate reader, and the final values were calculated from standard calibration plots [27][28][29].…”
Section: Determination Of Mda Total Thiol and No Metabolitesmentioning
confidence: 99%
“…The contents were then vortex-mixed and centrifuged, and the supernatants were transferred to a 96-well flat-bottomed microplate. Absorbance was read at 520 nm using a microplate reader, and the final values were calculated from standard calibration plots 19,20 .…”
Section: Determination Of No Metabolites (No 2 /No 3 )mentioning
confidence: 99%
“…[41] In contrast to these findings, it was shown that chronic treatment of female rats with high doses of esradiol has deleterious effects on learning and memory. [36] The results of the present study showed that the female rats with preposterous phase had a better performance in MWM compared with OVX rats. The results of passive avoidance test also showed that learning and memory procedures in animals with proestrus phase were better than OVX ones.…”
Section: Discussionmentioning
confidence: 58%
“…[1931323334] Learning and memory impairments, which have been reported in OVX rats confirm the beneficial effects of endogenous estradiol on learning and memory. [353637] The results of previous studies also indicated that estrogen therapy in OVX rats improves spatial learning and memory. [2238] Other researchers also showed that estrogen administration can reverse the effects of ovariectomy on avoidance and spatial memory.…”
Section: Discussionmentioning
confidence: 99%